Post-cardiac injury syndrome - Jaworska-Wilczyńska, Maria; Kuśmierczyk, Mariusz; Abramczuk, Elżbieta; Hryniewiecki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Post-cardiac injury syndrome (PCIS), also known as post-pericardiotomy syndrome, post-myocardial infarction syndrome, or post-commissurotomy syndrome, is a common complication after cardiac surgery, affecting approximately 40% of patients. PCIS occurs several days to several months after the surgical procedure. The syndrome manifests itself as exudative pericardial or pleural effusion with low-grade temperature and elevated inflammatory parameters. It is generally a self-limiting disease with a favorable prognosis, but it can have a relapsing course and be accompanied by life-threatening complications including cardiac tamponade and constrictive pericarditis.